Influence of Service Quality And Facilities on Visitor Satisfaction (New Royal Adventure Visitor Case Study) - Rias Aji Pangestu; Handoko, Trio Handoko; Zandra Dwanita Widodo (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the effect of: (1) Service Quality, (2) Facilities, on New Royal Adventure visitor satisfaction either partially or simultaneously. This type of research is quantitative using primary data types. Testing the analysis of data quality using validity and reliability tests. This study used a purposive sampling method where the samples taken were from certain consideration data which were generally adapted to the objectives and research problems and the sample in this study totaled 100 respondents who were visitors to New Royal Adventure. Data collection techniques in this study by distributing questionnaires with a Likert scale and directly with the respondents. The results of this study by means of the t test show that the variables of service quality and facilities have a positive and significant influence on New Royal Adventure visitor satisfaction. Also, the F test shows that the variables of service quality and facilities have a positive and significant influence on New Royal Adventure visitor satisfaction. While the results of the R2 coefficient test have an Adjusted R Square value of 52,1%, which means that the variable visitor satisfaction is influenced by the variables contained in this research and the remaining 47,9% is influenced by other variables outside of this study such as destination image, tourist loyalty, and product quality